Education for all addressing problems in primary schooling. - Baroy, Precious Jose. (2012)
It tackles some of the problems hounding the Philippine basic education sector and examines the various demand-side factors that hinder children from attending and completing primary school as well as maximizing their learning when they are in school.
Keywords: Basic education